Studi deskriptif pemanfaatan layanan corner di Perpustakaan IAIN Pekalongan - Arditya Prayogi; Nani Nuryani; Rhischa Assabet Shilla (Al-Kuttab : Jurnal Kajian Perpustakaan, Informasi dan Kearsipan, 2022)
Libraries can be briefly interpreted as a place to find information. This means that in every corner of the library an information search can be made. On this basis, the library has a service corner or literally interpreted as a corner. This article aims to describe the various corner services owned by the IAIN Pekalongan Library, as well as to analyze the problems faced in each corner service so that it can also produce an overview of efforts to solve the problems faced. This article uses a qualitative descriptive approach using the methods of observation, interviews, and literature study. From the results of the study, it was found that the IAIN Pekalongan Library serves five forms of corner services, namely: Corner Khazanah Pekalongan, BI Corner, Leyeh-Leyeh Corner, Studio Corner, and Multifunction Corner. Some of the problems faced in corner services at the IAIN Pekalongan Library include: lack of visitors, limited collections, dependence on funding, and lack of technical staff/librarians. Efforts made by the IAIN Pekalongan Library to overcome the problems that exist in its corner service include: conducting promotions, increasing the number of collections, conducting various collaborative efforts, and recruiting technical staff/librarians.